2020
DOI: 10.1111/apm.13068
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping of male breast cancer by PAM50 and immunohistochemistry: a pilot study of a consecutive Danish cohort

Abstract: Male breast cancer (MBC) is a rare disease that is still to be fully understood. In female breast cancer, molecular subtyping by gene expression has proven its significance. In this study, we characterize a consecutive cohort of MBC patients surgically treated from 1997 to 2017, identified at our institution (N = 37), and report the association between molecular subtypes found by a surrogate panel of immunohistochemical (IHC) markers, and the PAM50 signature, as well as risk of recurrence score and overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The present study showed that, when compared with women with the same subtypes, men had a significantly lower rate of pCR in HR+/HER2+ and a numerically lower rate of pCR in HR–/HER2+ breast cancer. Two prior studies evaluated the distribution of intrinsic subtypes by PAM50 in male breast cancer samples and identified that ≥90% were genomically luminal B or luminal A 10,11 . There was only one HER2+ case among both studies, and therefore the distribution of intrinsic subtypes within HER2+ male breast cancer remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study showed that, when compared with women with the same subtypes, men had a significantly lower rate of pCR in HR+/HER2+ and a numerically lower rate of pCR in HR–/HER2+ breast cancer. Two prior studies evaluated the distribution of intrinsic subtypes by PAM50 in male breast cancer samples and identified that ≥90% were genomically luminal B or luminal A 10,11 . There was only one HER2+ case among both studies, and therefore the distribution of intrinsic subtypes within HER2+ male breast cancer remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluated 67 MaBC samples by PAM50 and showed that 90% were luminal A or B 10 . Similarly, Christensen et al conducted PAM50 analysis in 37 MaBC samples and reported 95% of cases having luminal A or B subtype 11 . The high prevalence of luminal disease in men may be associated with lower sensitivity to NAC and in turn, lower rates of pCR compared with women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations